Harmonisasi Hukum Adat dan Prinsip Kesetaraan Gender di Desa Kemang Indah - Nada Marenza Putri; Victor Fernando Panjaitan; Nursal sabila; Shallomta Barus; M. Adya Zhafran; Maria Dwinoverine; Enriko Enriko; Indri Rizkiyani Kurnia; Exaudi Lestari Aruan (Universitas Katolik Widya Karya Malang, 2023)
Gender equality is a social construct related to the roles, rights, and characteristics of women and men in society that can change with evolving social dynamics. In Indonesia, gender equality issues are also tied to the principle of justice, which is an integral part of the state ideology, Pancasila. Customary law, on the other hand, is a legal system that develops within specific communities and is not always codified. Customary law in Kemang Indah Village, Riau, is strongly influenced by Islam and Islamic identity. The people of Kemang Indah Village are indigenous to the Kampar tribe and have a historical connection with Minangkabau, with strong Islamic influences evident in their customary law. This research aims to understand the relationship between customary law and the concept of gender equality in Kemang Indah Village. The results of the study show that the village community has successfully harmonized these two principles. Women in Kemang Indah Village have strong roles, even becoming leaders at various levels of community organization. They are also empowered to pursue their interests and talents, with facilities aligned with the applicable customary law. This is evidence that customary law principles can be integrated effectively with the concept of gender equality in the context of Kemang Indah Village. Thus, gender equality and customary law can coexist and mutually support each other in creating a fair and equal society in Kemang Indah Village.